Association between p62 expression and clinicopathological characteristics in oral leukoplakia. Issue 4 (25th June 2019) - Yoshida, Toshio; Terabe, Takehito; Nagai, Hiroki; Uchida, Fumihiko; Hasegawa, Shogo; Nagao, Toru; Miyabe, Satoru; Ishibashi‐Kanno, Naomi; Yamagata, Kenji; Warabi, Eiji; Gosho, Masahiko; Yanagawa, Toru; et al.
Abstract: Objective: Oral leukoplakia is keratinized lesions in the buccal mucosa, tongue, and gingiva. It is the most common oral precancerous lesion; oxidative stresses and irrelevant autophagy have been reported to be the cause of oncogenesis. p62, a cytoplasmic protein induced by oxidative stress, is an adaptor protein involved in the formation of protein aggregates and induction and inhibition of autophagy. The inhibition of autophagy induces p62 overexpression and promotes oncogenesis via the oncogenic signaling pathway. The aim of the present study was to elucidate the involvement of intracellular expression of p62 in oral leukoplakia and to address its potential clinical implementation as a biomarker to predict malignant transformation. Material and Methods: Fifty samples from subjects with confirmed oral leukoplakia were evaluated by immunohistochemical staining for the expression of p62, 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG), Ki67, and p53. Univariate and multivariate logistic regression analyses were performed to evaluate the association between p62, 8‐OHdG, Ki67, and p53 and clinical characteristics, including epithelial dysplasia. Results: Significant associations were observed between p62 expression in the nucleus, p62 aggregation, and epithelial dysplasia (adjusted odds ratio [OR] = 5.75; 95% confidence interval [CI]: [1.28, 26.2]; .024 and OR = 6.16; 95% CI: [1.01, 37.4]; .048, respectively). The expression of p62 in the cytoplasm and the levels of 8‐OHdG, Ki67, and p53 were not significantly associated with epithelial dysplasia. A significant relationship was found between p62 expression in the nucleus and p53 expression (OR = 3.94; 95% CI: [1.14, 13.6]; .031). Conclusions: The results suggested that p62 expression in the nucleus and p62 aggregation can be potential markers to predict the malignant transformation of oral leukoplakia.